(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the shoe factory’s availability of fixed assets, their structure, movement, and technical condition. A factor analysis of capital productivity and capital profitability is performed, key factors determining their dynamics are identified, and directions for improving the efficiency of fixed asset management are proposed.